2016
DOI: 10.18632/oncotarget.8674
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol and honokiol exert a synergistic anti-tumor effect through autophagy and apoptosis in human glioblastomas

Abstract: Glioblastoma (GBM) is a malignant brain tumor associated with a high mortality rate. The aim of this study is to investigate the synergistic effects of honokiol (Hono) and magnolol (Mag), extracted from Magnolia officinalis, on cytotoxicity and inhibition of human GBM tumor progression in cellular and animal models. In comparison with Hono or Mag alone, co-treatment with Hono and Mag (Hono-Mag) decreased cyclin A, D1 and cyclin-dependent kinase 2, 4, 6 significantly, leading to cell cycle arrest in U87MG and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 45 publications
(46 reference statements)
0
32
0
Order By: Relevance
“…Magnolol and honokiol, extracted from Magnolia officinalis , inhibit GB progression by inducing cell cycle arrest and decreasing the expression of p-PI3K, p-AKT, suggesting proliferation inhibition. In addition, the treatment with magnolol and honokiol exerts a synergistic antitumor effect also by inducing autophagy and apoptosis in GB cells ( 76 ). Li et al reported that endothelial-monocyte-activating polypeptide II (EMAP 2), a tumor-derived pro-inflammatory cytokine, promoted autophagic vacuole formation and inhibited the PI3K/AKT/mTOR signaling pathway, thereby inducing autophagy and inhibiting the viability, migration, and angiogenesis of GB ( 77 ).…”
Section: The Role Of Autophagy In Glioblastoma Therapy With the Phospmentioning
confidence: 99%
“…Magnolol and honokiol, extracted from Magnolia officinalis , inhibit GB progression by inducing cell cycle arrest and decreasing the expression of p-PI3K, p-AKT, suggesting proliferation inhibition. In addition, the treatment with magnolol and honokiol exerts a synergistic antitumor effect also by inducing autophagy and apoptosis in GB cells ( 76 ). Li et al reported that endothelial-monocyte-activating polypeptide II (EMAP 2), a tumor-derived pro-inflammatory cytokine, promoted autophagic vacuole formation and inhibited the PI3K/AKT/mTOR signaling pathway, thereby inducing autophagy and inhibiting the viability, migration, and angiogenesis of GB ( 77 ).…”
Section: The Role Of Autophagy In Glioblastoma Therapy With the Phospmentioning
confidence: 99%
“…The cytotoxicity of certain anti-tumor agents is induced by autophagy (29)(30)(31). To assess the association of autophagy with the pro-apoptotic effects of WZY-321, a number of autophagic markers were analyzed.…”
Section: Wzy-321 Enhances Autophagy In Shg-44 Glioma Cellsmentioning
confidence: 99%
“…It is now widely accepted that in response to various chemotherapeutic drugs, radiation, and targeted therapeutics, dying cells show large‐scale accumulation of autophagic vacuoles . Autophagy is also observed in the case of GBM in vitro and in vivo . TAM is widely accepted as a potent autophagy inducer .…”
Section: Introductionmentioning
confidence: 99%
“…22 Autophagy is also observed in the case of GBM in vitro and in vivo. 23,24 TAM is widely accepted as a potent autophagy inducer. 25 Graham et al 26 reported that TAM induces autophagic death in GBM cell lines and could provide new therapies for glioblastoma patients.…”
Section: Introductionmentioning
confidence: 99%